Interrelationships Among Weed Management in Coffee Plantation and Soil Physical Quality - Araujo-Junior, Cezar Francisco; Junior, Moacir de Souza Dias; Alcântara, Elifas Nunes de; Guimarães, Paulo Tácito Gontijo; Ajayi, Ayodele Ebenezer (IntechOpen, 2012)
None